Pertumbuhan Bibit Kopi Liberika Tungkal Komposit pada Aplikasi Pupuk Kandang Ayam - Lizawati, Lizawati; Kartika, Elis; Latief, Madyawati; Tarigan, Indra Lasmana; Sutrisno, Sutrisno; Puspitasari, Ratih Dyah (Jurnal Agroekoteknologi, 2024)
One of the efforts to increase the growth of Liberica coffee of Tungkal composite seedlings is through organic fertilization as considered inorganic fertilizers replacement. The purpose of this study was to look for the best dose of chicken manure for the growth of Liberica coffee of Tungkal composite seedlings. This study used a randomized block design with 4 replications with one factor, namely chicken manure consisting of 7 treatment levels, namely 0, 50, 100, 150, 200, 250 and 300 g of chicken manure/polybag. The variables observed were increase in seedling height, increase in stem diameter, increase in number of leaves, leaf area, crown dry weight, and root dry weight. The results showed that the application of chicken manure was able to increase the increase in seedling height, increase in stem diameter, increase in the number of leaves, and crown dry weight of liberica coffee seedlings, but was not able to increase leaf area and root dry weight. The recommended dose of chicken manure to increase the growth of liberica coffee seedlings was 211 g of chicken manure/polybag.